Law in the Age of Disruption: Multidisciplinary Insights on Emerging Technologies and Legal Evolution - Chuphal, Garima; Vohra, Jigyasa; Sharma, Sandeep Kumar; Minhajuddin, Md.; Ahmad, Wasim; Baba, K Rama Krishna (Journal of Neonatal Surgery, 2025)
The 21st century has experienced unmatched technological breakthroughs that are basically changing the framework of law systems across the globe. The disruptive power of new tech includes artificial intelligence, blockchain, biotechnology, and quantum computing, and the legal theory has new challenges and opportunities in the area of regulation and enforcement. The present paper is a discussion of the interactive nature of law and disruptive technologies and on why the law should be reformed in a multidisciplinary manner. It relies on the wisdom of such fields as computer science, ethics, sociology, and economics to examine the way legal systems can become dynamic so that justice, accountability, and democratic governance can be secured in the fast changing digital world.